2022
DOI: 10.3390/microorganisms10081516
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacteria: Ecology and Impact on Animal and Human Health

Abstract: Nontuberculous mycobacteria (NTM) represent an important group of environmentally saprophytic and potentially pathogenic bacteria that can cause serious mycobacterioses in humans and animals. The sources of infections often remain undetected except for soil- or water-borne, water-washed, water-based, or water-related infections caused by groups of the Mycobacterium (M.) avium complex; M. fortuitum; and other NTM species, including M. marinum infection, known as fish tank granuloma, and M. ulcerans infection, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
1
5
0
2
Order By: Relevance
“…This could be caused because the tissues were fixed in formalin for a long period and, consequently, the DNA could be degraded. On the other hand, the mycobacteria found may have been transmitted by water [ 34 ] and, according to the results of our study, the possibility that the mycobacteria were present in the water tanks of the Syngnathids should be highlighted. Further studies with the aim of investigating the possible origin of the mycobacterial contamination should be conducted.…”
Section: Discussionsupporting
confidence: 51%
“…This could be caused because the tissues were fixed in formalin for a long period and, consequently, the DNA could be degraded. On the other hand, the mycobacteria found may have been transmitted by water [ 34 ] and, according to the results of our study, the possibility that the mycobacteria were present in the water tanks of the Syngnathids should be highlighted. Further studies with the aim of investigating the possible origin of the mycobacterial contamination should be conducted.…”
Section: Discussionsupporting
confidence: 51%
“…Firstly, NTM-PD is caused by environmental NTMs that have been found in soil, dust, water, and even in animals, which highlights the importance of environmental and animal health in NTM-PD prevention ( Lopeman et al., 2019 ; To et al., 2020 ). Measures such as better sanitation, proper disposal of animal waste, and the reduction of environmental pollution can potentially reduce the risk of NTM-PD transmission ( Pavlik et al., 2022 ). Secondly, the study found that impaired immune function is a high-risk factor for NTM-PD.…”
Section: Discussionmentioning
confidence: 99%
“…Current research is focused on the incidence of NTM in bats. It was found that NTMs are abundant in bat faeces (up to 2 h) and subsequently in their guano (faeces older than 2 h; Modra et al, 2017;Pavlik et al, 2022a). It was even found that they are also contained in garden substrates with bat guano (unpublished data).…”
Section: ***mentioning
confidence: 97%
“…La investigación actual se centra en la incidencia de NTM en murciélagos. Se encontró que las NTM son abundantes en las heces de los murciélagos (hasta 2 h) y posteriormente en su guano (heces de más de 2 h; Modra et al, 2017;Pavlik et al, 2022a). Incluso se comprobó que también están contenidos en sustratos de jardín con guano de murciélago (datos no publicados).…”
Section: ***unclassified